Overview of Storage and Distribution of Medical Supplies at the Sunggal Community Health Center in 2024 - Mutiara Ashifa; Syahputra Siregar, Yusuf; Aulia Putri, Ghizka; Fiqhi Ranu Mahendra, Akmal; Makmur Siregar, Rizki; Doanita Hasibuan, Indah (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
A community health center (Puskesmas) is a facility that provides primary health care services to both the general public and individuals. The storage and distribution of medical supplies is crucial to health service management at the Puskesmas. The purpose of this study was to determine the overview of the storage and distribution of medical supplies at the Sunggal Community Health Center in 2024. This study used descriptive observational interviews with the person in charge of the pharmacy department. Data collection used purposive sampling in the warehouse or drug room of the Sunggal Community Health Center in Medan on Thursday, November 14, 2024. The results of the study showed that the storage and distribution of medical supplies at the Sunggal Community Health Center in 2024 was very good (100%), spatial arrangement (93.3%) (very good), and drug distribution (100%) (very good). However, there is still 1 parameter of spatial planning regulations that does not meet the standards or targets, namely large-scale storage only in cupboards and on shelves, which should be based on Permenkes 74 of 2016, large-scale drugs are stored on pallets. This shows that the description of the storage and distribution of health supplies at the Sunggal Health Center in 2024 meets storage standards. The storage and distribution pattern of health supplies in the pharmacy warehouse still needs improvement in order to maintain the quality of health supplies in the pharmacy room and warehouse, optimization of storage and distribution of health supplies is very important to ensure the availability and quality of health services at the Sunggal Health Center.